White-coat hypertension by ambulatory blood pressure monitoring in individuals with elevated office blood pressure and correlation with co-morbidities - Durugu, Sasank; Rao, Srinivasa (International Journal Of Community Medicine And Public Health, 2022)
Background: White-coat hypertension characterized by elevated office blood pressure and normal ambulatory blood pressure monitor measurements has an incidence of 10-30%. It is considered that white-coat hypertension is not entirely benign condition and progression to hypertension has been identified in some cases. Methods: 197 consecutive subjects with elevated office blood pressure measurements were evaluated by ambulatory blood pressure monitoring and assessed for co-morbidities. Results: Of the 197 subjects evaluated 138 (70.05%) had hypertension and 59 (29.95%) had white-coat hypertension. Diabetics comprised of 21.73% of hypertensive individuals and 25.42% of white-coat hypertension individuals (p value 0.57). Similarly, when assessed for body mass index and dyslipidemia there was no statistically significant difference in both the groups. Conclusions: White-coat hypertension is a common condition and proper assessment by ambulatory blood pressure monitoring to diagnose the condition can avoid unnecessary antihypertensive medication. Identification of other co-morbidities could lead to appropriate management goals.